Illus Izauryjczyk wobec uzurpacji Bazyliskosa - Leszka, Mirosław J. (Acta Universitatis Lodziensis. Folia Historica, 2005)
Hereby paper was dedicated to Illus Isaurian’s part played in events connected with Basiliscus’ usurpation in years of 475-476. At the stage of preparations to Basilicus’ usurpation, Illus acted as an intermediary between Basiliscus and Armatos and Verina. Zeno’s debar from posts of authority went on without bloodshed, without armed lighting, with the main part played by Verina and Basiliscus. In those circumstances most of sources take no account of Illus’ participation in those events. Under the reign of Basiliscus, Illus, who was charged with a task of Zeno’s removal, proved his abilities as an efficient politician. He was able to notice,’that Basiliscus is unable to stabilize his reign. Having estimated the state of affairs Illus decided to go over Zeno’s side and he supported Zeno in his return to authority, which enabled him to obtain the strong position at the Emperor’s side. It doesn’t seem that Zeno and Illus have ever had friendly relations with each other. Their relations were merely based on common political interest, at given moment.